Bitcoin and Beyond Cryptocurrencies, Blockchains and Global Governance - Campbell-Verduyn, Malcolm (Taylor & Francis, 2017)
This volume brings scholars of anthropology, economics, Science and Technology Studies, and sociology together with global political economy scholars in assessing the actual implications posed by Bitcoin and blockchains for contemporary global governance. Its interdisciplinary contributions provide academics, policymakers, industry practitioners and the general public with more nuanced understandings of technological change in the changing character of governance within and across the borders of nation-states.